ORIBATID MITES FAUNA (ACARIFORMES, ORIBATIDA) OF COASTAL ECOSYSTEMS AND ISLANDS OF NORTH-WEST PART OF THE CASPIAN SEA AND THEIR LIFE FORMS - G. M. Abdurakhmanov; A. A. Grikurova; U. Ya. Shtanchaeva; L. S. Subias (Юг России: экология, развитие, 2014)
The article presents the results of the study of oribatid mites of coastal ecosystems and of islands of the north-west part of the Caspian Sea: species composition, distribution data and analysis of life forms of oribatid mites.